Sub-Conscious Decision Mapping and Network Framework for Retail Market Consumption - Chatterjee, Shuvam; Kundu, Aritra (Indian Journal of Marketing, 2020)
Todayâ€™s world of marketing is a highly dynamic and volatile place due to high competitive clutter, and hence, every industry needs to accept the understanding of impulsive change as a new standard. This article focused on understanding brand awareness of consumers from an embedded cognitive state. Consumer’s decision making for a brand mainly results from both conscious and non-conscious experiences that a consumer has been exposed to. Consumers preserve this brand knowledge in a non-conscious level of their mind. Marketers depend upon the use of multi-sensory metaphors to bring out that digged-in knowledge. This paper introduced ZMET as a method to elicitate hidden understanding about a consumerâ€™s decision making process by stimulating human senses and understanding about the attributes that ultimately contribute in consumer decision making. The research threw light on a qualitative example considering the wellness industry by identifying the hidden metaphors that contributed in understanding the consumer’s satisfaction.